(untitled) (Proceedings OPTIMAL, 2025)
Maternal behavior typically influences early childhood oral health such as caries. This is relied on the mother’s confidence and perceived ability to manage her child’s dental care. Within the framework of the Theory of Planned Behavior (TPB), perceived behavioral control (PBC) serves as a crucial determinant of intention and subsequent preventive actions. However, limited research in Indonesia has examined how maternal PBC influences the intention to maintain children’s oral health. This study aimed to analyze the correlation between maternal perceived behavioral control and the intention to maintain oral health among kindergarten children. A cross-sectional, multivariate design was applied involving 305 mothers selected through cluster random sampling from seven kindergartens. Data were collected using structured questionnaires measuring perceived behavioral control with 18 questions and intention toward dental care with 16 questions, each rated on a 4-point ordinal scale. Data analysis was performed using ANOVA regression with a significance level of p < 0.05. The mean perceived behavioral control score was 51.23 ± 7.95, while the mean intention score was 46.44 ± 7.44. Regression analysis revealed a strong and significant correlation between PBC and intention (β = 0.635; R² = 0.713; p < 0.001), indicating that 71.3% of the variance in maternal intention could be explained by perceived behavioral control. In conclusion, maternal PBC has a strong predictive influence on mothers’ intention to maintain children’s oral health.